Problematika Santri Menghafal Al-Quran Di Pondok Pesantren Tahfidzul Quran Asy Syadzili 3 Tumpang Malang Jawa Timur - Ni'matus Sholihah; Muhammad Mahfud; Barudin (Jurnal Pendidikan Agama Islam Miazhar, 2025)
Asy Syadzili 3 Tahfidzul Quran Islamic Boarding School has an additional program of one juz per month. With this program it is hoped that students will be able to complete the memorization within three years. However in reality, many students experience several internal and external obstacles in completing the memorization according to the islamic boarding school program. This research was conducted to describe the problems and solutions to overcome the problems faced by students in memorizing the al-Quran at PPTQ Asy Syadzili 3. This research uses a qualitative approach which is descriptive qualitative and field research. Research result show that: 1) The problems experienced by students in memorizing the al-Quran is laziness and boredom, the students’ability to read the al-Quran, often forgetting verses, a crowded environment, not being able to manage time, friends, and lots of thoughts. 2) Solutions to the problems experienced by students in memorizing the al-Quran in the form of motivations and different systems for reciting the al-Quran, providing learning and accompaying teachers, consistent murojaah, administrators and giving sanctions, obeying the rules and schedule of islamic boarding school activities, increasing individuaal awareness, maintaining friendly attitudes, completing work, and positive thingking.